Evaluation of axial load-bearing capacity of concrete columns strengthened by a new section enlargement method - Hao, Meijing; Zheng, Wenzhong; Chang, Wei (Journal of Civil Engineering and Management, 2022)
The objective of this study is to evaluate the axial load-bearing capacity of section-enlargement concrete columns. To reach the objection, a new strengthened method in which columns are jacketed with a large welded octagonal stirrup at the center and four spiral stirrups at the corners of column is developed. The new section-enlargement method avoids interrupting existing columns and improves the reliability of strengthened part, besides, the confining stress generated by octagonal stirrup and spiral stirrups enhances the compressive strength and deformability of strengthened columns. In addition, sixteen large-scale concrete columns strengthened by the new strengthened method were tested under axial compressive loads. The experimental results show that the axial compression ratio of existing column generates stressstrain lag in strengthened part and decreases the load-bearing capacity of specimens; the stirrups in strengthened part significantly enhance the axial load-bearing capacity of specimens. According to confinement conditions, the cross-section of specimens is divided into five parts and the confinement factor for each part is calculated to establish the prediction models for the load-bearing capacity of specimens. Furthermore, by comparing the results between the developed model and existing models, the developed model has high accuracy in evaluating the load-bearing capacity of strengthened columns.First published online 20 December 2021